External Debt Statistics : Guide for Compilers and Users. (Manuals and Guides, 2005)
This Guide provides clear, up-to-date guidance on the concepts, definitions, and classifications of the gross external debt of the public and private sectors, and on the sources, compilation techniques, and analytical uses of these data. The Guide supersedes the previous international guidance on external debt statistics available in External Debt: Definition, Statistical Coverage, and Methodology (known as the Gray Book), 1988. The Guide's conceptual framework derives from the System of National Accounts 1993 and the fifth edition of the IMF's Balance of Payments Manual(1993). Preparation of the Guide was undertaken by an Inter-Agency Task Force on Finance Statistics, chaired by the IMF and involving representatives from the BIS, the Commonwealth Secretariat, the European Central Bank, Eurostat, the OECD, the Paris Club Secretariat, UNCTAD, and the World Bank.